Indian Immigrants in Lahiri’s The Namesake: Diasporic Identity Process - Kifayatullah; Khan, Abdul Hamid (International Journal of Psychosocial Rehabilitation, 2020)
—Jumpha Lahiri’s The Namesake (2003) narrates the clash between western and eastern cultures. This qualitative study intends to describe firstly problems faced by Indian immigrants caused by displacement namely identity crisis, cultural clashes, alienation, and unhomeliness in The Namesake, and secondly how they cope with diasporic situation by adopting mimicry, hybridity, and ambivalence. Bhabha’s noticeable theories of displacement, mimicry, hybridity and ambivalence in The Location of Culture are applied in the analysis of this study to describe the main characters mimicry, hybridity and ambivalence in The Namesake. This study reveals that; first, the main characters of The Namesake, in order to fight their displacement and to get acceptable, perform mimicry, hybridity in their manners and actions. Second, ambivalence represented by the characters in the novel as a tug of war between resisting and accepting the western culture. In conclusion, the main characters’ mimicry, hybridity and ambivalence in ﺍLahiri’s ﺍThe ﺍNamesake is ﺍthe result ﺍof cultural clashes between eastern and western cultures.